STUDY THE PROPERTIES OF THERMOTROPIC LIQUID CRYSTALS INDUCED BY HYDROGEN BONDING BETWEEN PYRIDYL- HETEROCYCLIC DERIVATIVES AND BENZOIC ACID, 4-HEPTYLOXYBENZOIC ACID OR 4-OCTYLOXYBENZOIC ACID - Jber, Nasreen Raheem (Al-Nahrain Journal of Science, 2018)
Synthesis of new derivatives of heterocyclic compounds such as (Triazoles, tetrazole, oxazoleand thiadiazole). Liquid crystalline complexes have been obtained from binary mixtures of(4-pyridyl) heterocyclic derivatives with benzoic acid, 4-heptyloxychlorobenzoic acid or4-octyloxybenzoic acid. The (4-pyridyl) heterocyclic derivatives are not mesomorphic, but theH-bonded complexes are showed droplets nematic texture which is developed from threadednematic on slow heating. Their liquid crystalline properties were investigated by polarizing opticalmicroscopy.